The Effect of Cultural Factors and Peers’ Reference on Online Buying Behavior - Ertugan, Ahmet; Zeiadeh, Mohammad (Journal of Economic, Administrative and Legal Sciences, 2018)
Cultural factors and peers’ references are considered as a part of the buyer decision models in traditional as well as online shopping. This study aimed to determine the impact of cultural factors (Cultural values, religious orientation, peer’s reference, openness to technological innovation, communication forms, patterns and expectations) on online buying behavior in Jordan from the perspective’s postgraduate students at Yarmouk University. The study is based on the descriptive analytical approach through the questionnaire which was distributed to a sample consisting of (412) students were selected in a way of simple random sample from the university faculties. The results of the study showed that there was a statistically significant positive effect of (cultural values, openness to technological innovation and communication forms, patterns and expectations) on internet buying, and there was a statistically significant negative impact of peers’ reference on the adoption of internet buying, while there was no statistically significant impact of religious orientation on the adoption of internet buying behavior.